The Investigational Clinical Center: a clinical-supportive and patient-centered trial unit model. Ten years of experience through normal and pandemic times of a large pediatric trial center in Italy - Giuseppe Pontrelli; Marco Ciabattini; Franco De Crescenzo; Isabella Biondi; Rossana Cocchiola; Giorgia Copponi; Claudia Frillici; Francesca Molinari; Francesca Rocchi; Alessandra Simonetti; Paolo Rossi; Susanna Livadiotti (BMC, 2021)
Abstract Evidence-based medicine relies on appropriately designed, conducted and reported clinical trials (CTs) to provide the best proofs of efficacy and safety for pharmacological and non-pharmacological treatments. Modern clinical research features high complexity and requires a high workload for the management of trials-related activities, often hampering physicians' participation to clinical trials. Dealing with children in clinical research adds complexity: rare diseases, parents or legal guardian reluctance to engage and recruitment difficulties are major reasons of pediatric trials failure. However, because in pediatrics many treatments are prescribed off-label or are lacking, well-designed clinical trials are particularly needed. Clinical Trial Units (CTUs) are indeed an important asset in the implementation of clinical trials, but their support to investigators is limited to administrative and non-clinical tasks. In this paper we present the model of the Investigational Clinical Center (ICC) of the Bambino Gesù Children's Hospital in Rome. The ICC includes clinicians supporting the Principal Investigators for clinical management of enrolled patients in compliance of Good Clinical Practice, the legal framework of Clinical Trials. Furthermore, we present 10 years' experience in pediatric clinical trials and how it has been affected in 2020 by the COVID-19 pandemic. The activity of the ICC has been evaluated according to specific metrics of performance. The ICC model offers a complete support, helping investigators, patients and their families to overcome majority of barriers linked to clinical research, even in time of pandemic. We propose this organization as an innovative model for total-supportive and patient-centered clinical trial implementation.